Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Grave markers of Fannie F. Watkins (1886-1977) and Jack Watkins, Jr. US Army (6/11/1909-12/24/1975) Chattanooga Memorial Park